Extraction and functional properties of protein from de-oiled rice bran - Jongjareonrak A. (Chiang Mai University, 2015)
The de-oiled Sangyod Phatthalung (Oryza sativa L.) rice bran waste from screw-press, rice bran oil production contains 12.8% protein. It was used to study the optimization of protein extraction. An optimization procedure using a central composite design (CCD) with three factors -sodium hydroxide concentration (0.05-0.2 M), extraction temperature (30-60°C) and extraction time (60-240 min) - determined the effect of these parameters on extraction yield and functional properties of rice bran protein. The optimum conditions obtained by using response surface methodology (RSM) were a sodium hydroxide concentration of 0.13 M at an extraction temperature of 49°C for 170 min. The predicted protein extraction yield for these optimum conditions was 45.2%. A verification experiment was conducted under optimum conditions and the protein extraction yield was 43.1%. The experimental and predicted values were similar, confirming that the prediction model equation was capable of reasonably and accurately predicting the protein extraction yield. The rice bran protein extract exhibited a maximum solubility at pH 10 (68.3%). The foaming activity, foaming stability, emulsifying activity index (EAI) and emulsion stability index (ESI) values of the rice bran protein at pH 10 were 113.4% v/v, 62.6 min, 0.170 (Abs500nm) and 37.1 min, respectively. These results indicated that protein can be extracted from de-oiled Sangyod Phatthalung rice bran with a high yield and can be used as a food ingredient or protein source.